2019
DOI: 10.1002/cbf.3398
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term in vitro treatment with telomerase inhibitor MST‐312 induces resistance by selecting long telomeres cells

Abstract: Telomerase is a good target for new anticancer drug development because it is present in over 85% of human tumours. However, despite chronic therapy is a condition for anti-telomerase approach, the effects of long-term treatment with telomerase inhibitors remain not well understood. In this work, it was evaluated the effects of long-term treatment of human MDA-MB-231 breast cancer cells with the telomerase inhibitor MST-312. Cells were treated for 72 hours or 140 days, and it was accessed their viability, prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Then, it is interesting to investigate candidate drugs for combination therapy in lung cancer to avoid treatment failure. Since a long‐term treatment with MST‐312 on breast cancer cells increased chemosensitivity to docetaxel and irinotecan (classical drugs for breast cancer treatment), (Morais et al, 2019) we investigated chemosensitivity to cisplatin and observed no difference between treated and nontreated H460 cells. However, the combination of long‐term treatment with MST‐312 and short‐term exposure to cisplatin did not alter the viability of H460 cells when compared with cells treated with DMSO.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, it is interesting to investigate candidate drugs for combination therapy in lung cancer to avoid treatment failure. Since a long‐term treatment with MST‐312 on breast cancer cells increased chemosensitivity to docetaxel and irinotecan (classical drugs for breast cancer treatment), (Morais et al, 2019) we investigated chemosensitivity to cisplatin and observed no difference between treated and nontreated H460 cells. However, the combination of long‐term treatment with MST‐312 and short‐term exposure to cisplatin did not alter the viability of H460 cells when compared with cells treated with DMSO.…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal and lung cancer cell lines, it was demonstrated that clonogenic potential is positively modulated by hTERT independently of its canonical activity (Khattar et al, 2016). Morais et al (2019) demonstrated that chronic exposure to MST-312 led to the selection of breast cancer cells with longer telomeres and that intratumoral heterogeneity played an important role in the survival of cells throughout the treatment. They demonstrated that MST-312 had an increased cytotoxic effect in clonal MDA-MB-231 cells in comparison with the parental cell line (Morais et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown to inhibit TERT activity and reduce telomere length in cultured cancer cells without causing acute cytotoxicity, however, its efficacy is highly telomere length-dependent, so that it may not be an ideal single therapy agent for most cancers [ 5 , 180 ]. In addition, MST-312, the synthesized tea catechin EGCG analogue, was observed to potently inhibit telomerase activity in different types of malignant cells [ 182 , 183 ]. An epigenetic mechanism may be involved in the down-regulation of TERT expression mediated by EGCG and MST-312 [ 184 ].…”
Section: Implications Of Cancer-related Telomere Maintenance In Precimentioning
confidence: 99%